2020
DOI: 10.3390/atmos11050489
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Adhesion Force of Individual Aerosol Particles by Atomic Force Microscopy

Abstract: A new method, namely, force–distance curve mapping, was developed to directly measure the adhesion force of individual aerosol particles by atomic force microscopy. The proposed method collects adhesion force from multiple points on a single particle. It also takes into account the spatial distribution of the adhesion force affected by topography (e.g., the variation in the tip angle relative to the surface, as well as the force imposed upon contact), thereby enabling the direct and quantitative measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…After dry sedimentation or wet sedimentation, atmospheric particles will participate in biogeochemical cycle (Mahowald et al, 2018;Luo et al, 2019). It is known that large amounts of mineral particles are carried into the atmosphere by strong ground winds and transported over long distances (Adachi et al, 2020;Ono et al, 2020). Long-distance transport of mineral particles can alter biogeochemical processes on land and in the ocean.…”
Section: Airborne Particles and Global Geochemical Cyclingmentioning
confidence: 99%
“…After dry sedimentation or wet sedimentation, atmospheric particles will participate in biogeochemical cycle (Mahowald et al, 2018;Luo et al, 2019). It is known that large amounts of mineral particles are carried into the atmosphere by strong ground winds and transported over long distances (Adachi et al, 2020;Ono et al, 2020). Long-distance transport of mineral particles can alter biogeochemical processes on land and in the ocean.…”
Section: Airborne Particles and Global Geochemical Cyclingmentioning
confidence: 99%
“…It was found that composite films have greater adhesion than pure aluminum films. An atomic force microscope (AFM) is commonly used for determining the adhesion force [21][22][23]. In this regard, Johnson-Kendall-Roberts (JKR), Derjaguin-Muller-Toporov (DMT) and Hertzian theory (HERTZ), which are theoretical models, are regularly used [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…To further verify this conclusion, the force between the calcium fluoride particles in the presence and absence of sulfate was measured using probes with modified calcium fluoride particles (see details in Text S6). Compared with the control group, the adhesion between the calcium fluoride particles increased in the presence of sulfate (Figure d). From the typical force curve, the presence of sulfate increased the adhesion force between calcium fluoride particles from 1.62 to 2.46 nN, a 50% increase (Figure e,f).…”
Section: Resultsmentioning
confidence: 99%